THE EFFECT OF AUDITOR COMPETENCE, EMOTIONAL INTELLIGENCE OF AUDITORS, AND AUDITOR INDEPENDENCE ON AUDITOR PERFORMANCE - Hariati Karo; Harlyn Siagian (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2018)
This study was conducted to determine the effect of auditor competence on auditor performance, to determine the effect of auditor emotional intelligence on auditor performance, to determine the effect of auditor independence on auditor performance and to determine the effect of auditor competency, auditor emotional intelligence, and auditor independence on auditor performance at 3 Offices Public Accountant (KAP) in Jakarta. The variables studied were auditor competency variables, auditor emotional intelligence variables, and auditor independence variables as independent variables and auditor performance as the dependent variable. The method used in this research is the descriptive method, where data is obtained by distributing questionnaires to 43 auditors, analyzed using SPSS Software and given conclusions. From the results of the study, the auditor's competency level is below the average, which means that the auditor does not have good competence. The level of emotional intelligence above average means that the auditor has good emotional intelligence. The level of auditor independence is above the average, which means that the auditor has good independence. The level of auditor performance is above the average, which means that 3 KAPs in Jakarta have good auditor performance. There is no significant effect on auditor competence on auditor performance by 0.090, there is a significant effect on auditor emotional intelligence on auditor performance by 0.000, there is a significant effect on auditor independence on auditor performance by 0.008, and there is also a significant influence on auditor competence, auditor's emotional intelligence, and auditor independence simultaneously on auditor performance at 7,112 with a significance value of 0.001